Analysis of the Distribution and Transmission Law of Vibration Energy of Planetary Gear - Wu Yuchao; Ma Chaofeng; Liu Kai; Fu Yu; Dou Kai (Jixie chuandong)
Based on a torsional- transverse coupling model of a 2K- H spur planetary gear,the formula of vibration energy of the planetary gear transmission system is derived. The strain energy and kinetic energy of vibration of the planetary gear are calculated for four planetary gears under the operation condition,in which the ring gear is fixed. The distribution characteristic of vibration energy of the planetary gear is summarized. Without considering friction and damping of the planetary gear,the law of transmission of vibration energy of the planetary gear is obtained at the same and different orders of vibration.